Genetliaci nella fattoria. Denominazioni di animali sul conteggio degli anni (Atti del Sodalizio Glottologico Milanese, 2014)
This paper is about Italian Dialects denominations of domesticated animals in accordance to their age. A number of observations can be made considering the changes of denominations of the animals during the time span of their life. The different terminologies are thoroughly treated in their etymological aspects. The first year of life shows denominations different from the second and the third years. Many different denominations are listed from different traditions: the Italian Dialects are compared with other languages and the overall terminology receives a complete etymological classification. KEYWORDS: Italian dialects, animal names, etymology, lexicon, lexical typology